Assessment Instrument Development for Maharah Qira'ah: A Case Study on Qira'ah Rasyidah Book Volume 5 - Siregar, Amy Fitriani; Muhajir, Muhajir; Septika Bayzura; Kamilatus Salsabila; Alin Safaraz Himam; Nila Alfiroh (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
The problem with maharah qira'ah assessment instruments is that there is no standardized assessment tool in Qira'ah Rasyidah volume 5, which limits access to effectively measuring students' reading skills. This research aimed to develop assessment instrument of the Qira'ah Rasyidah book volume 5, while the contains of this book were merely scripts, Arabic texts or stories; without any assessment instrument. In the results of the analysis, this book does not have any form of assessment instrument so it is not easy to assess comprehension, critical thinking, and analytical skills in reading Arabic texts. The research method in this research was qualitative of literature study data collection. The primary data source consisted of an in-depth analysis of the materials in Qira'ah Rasyidah volume 5, focusing on its content structure, language complexity, and the absence of assessment instruments. The secondary data source was taken from articles, information books, and literature documents relevant to this research. In addition, the results showed that the development of a suitable test assessment for reading skills in this book is at the fifth level, the ability to evaluate. The development results were categorized into three types of tests including pronunciation, answer selection, and essay tests.  The findings of this study contribute to the advancement of Arabic language assessment by providing a structured assessment instrument for Qira'ah Rasyidah volume 5. This research served as a basis for future curriculum development, ensuring that assessment tools were aligned with higher order thinking skills in Maharah Qira'ah.